Voltage Tracking of a DC-DC Flyback Converter Using Neural Network Control - Buswig, Yonis.m.yonis; Utomo, W.M; Yi, S.S.; Haron, Z.A.; Bakar, A.A.; Ahmad, M.Z (Institute of Advanced Engineering and Science (IAES), 2012)
This paper proposes a neural network control voltage tracking scheme of a DC-DC Flyback converter. In this technique, a back propagation learning algorithm is employed. The controller is designed to improve performance of the Flyback converter during transient and steady state operations. Furthermore, to investigate the effectiveness of the proposed controller, some operations such as starting-up and reference voltage variations are verified. The numerical simulation results show that the proposed controller has a better performance compare to the conventional PI-Controller method.